Lateral Center-Edge Angle Is Not Predictive of Acetabular Articular Cartilage Surface Area: Anatomic Variation of the Lunate Fossa. Issue 8 (July 2020) - Trinh, Thai Q.; Leunig, Michael; Larson, Christopher M.; Clohisy, John; Nepple, Jeff; Zaltz, Ira; Kelly, Bryan T.; Naimark, Micah B.; Bedi, Asheesh
Background: Surgical treatment of symptomatic femoroacetabular impingement (FAI) and dysplasia requires careful characterization of acetabular morphology. The lateral center-edge angle (LCEA) is often used to assess lateral acetabular anatomy. Previous work has questioned the LCEA as a surrogate for acetabular contact/articular cartilage surface area because of the variable morphology of the lunate fossa. Hypothesis: We hypothesized that weightbearing articular cartilage of the acetabulum would poorly correlate with LCEA secondary to significant variation in the size of the lunate fossa. Study Design: Cohort study (Diagnosis); Level of evidence, 3. Methods: Patients with 3D CT imaging undergoing either hip arthroscopy or periacetabular osteotomy for FAI or symptomatic hip instability were retrospectively identified. The LCEA and femoral head diameter were measured on an anteroposterior pelvis radiograph. Patients were grouped according to their lateral acetabular coverage as undercoverage (LCEA, <25°), normal coverage (LCEA, 25°-40°), or overcoverage (LCEA, >40°). Patients were randomly identified until each group contained 20 patients. The articular surface area was measured from preoperative 3D CT data. Linear regression analysis was performed to examine the relationship between articular surface area and LCEA. Continuous and categorical data were analyzed utilizing analysis of variance and chi-square analysis. Statistical significance was set at P < .05. Results: No difference in age ( P = .52), body mass index (BMI) ( P = .75), or femoral head diameter ( P = .66) was noted between groups. A significant difference in articular surface area was observed between patients with undercoverage and those with overcoverage (20.4 cm 2 vs 24.5 cm 2 ; P = .01). No significant difference was identified between the undercoverage and normal groups (20.4 cm 2 vs 23.3 cm 2 ; P = .09) or the normal and overcoverage groups (23.3 cm 2 vs 24.5 cm 2 ; P = .63). A moderate positive correlation was observed between LCEA and articular surface area across all patients ( r = 0.38; P = .002) but not when patients with undercoverage were excluded ( r = 0.02; P = .88). Significant variation in surface area was observed within each group such that no patient in any group was outside of 2 SDs of the means of the other groups. When patients were categorized into quartiles established by the articular surface area for the entire population, 40% of patients with overcoverage were observed in the first or second quartile (lower area). Conclusion: Lateral acetabular undercoverage based on the LCEA (<25°) correlates with decreased acetabular surface area. Normal or increased acetabular coverage (LCEA, >25°), however, is not predictive of increased, normal, or decreased acetabular surface area.